Impact pressure of breaking waves - Chen, Ping Ho; Ackermann, Norbert L.; Arbhabhirama Anat; Shuto, Nobuo; Asian Institute of Technology (Bangkok : Asian Institute of Technology, 1973)
Shock pressures caused by impact between a solid and a liquid have been studied theoretically as well as experimentally. Bagnold' s model was used to derive the shock pressure by applying the concept of virtual mass. The validity of this model was conformed in the present investigation. The air entrapped between the impacting solid and the liquid plays an important role in deterring shock pressures. The effect of air on the shock pressure was studied by hanging the thickness of air cushion and the ambient air pressure in the apparatus used to determine impact pressures. The experimental results show a consistent trend with that calculated by using Bagnold's model. For a fixed thickness of air cushion, the shock pressure increases with the increase of the air pressure. For a fixed air pressure, the shock pressure is inversely proportional to the thickness of the air cushion.
A thesis submitted in partial fulfillment of requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1973
Keywords: Shock waves; Shock (Mechanics)